Legal bases of innovative activiti and its implementation in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
This article deals with the questions concept an innovation, value of the innovative process, a specialassessment of profitability of innovative service, its influence on development of the state economy, thenational and regional legal streamlining connected with this area, innovation financing, innovative programsand projects, constitutional and legal bases of innovative and industrial development .Keywords: National and innovative fund, Legal bases, Constitution, Code, Strategy.